INTERVENTIONS TO REDUCE STUNTING IN RURAL AREA: A SYSTEMATIC REVIEW - Siti Marina Wiastuti; Tantut Susanto; Iis Rahmawati (UPT Penerbitan Universitas Jember, 2023)
Background: Stunting is a world health problem that affects nearly 149.2 million children under five. The incidence of stunting is more in rural areas. Both specific and sensitive nutrition interventions are needed to reduce stunting. This study aims to provide an overview of interventions to overcome stunting in rural areas for 1000 days of life. Methods: The research method is a literature review with the PRISMA approach. A literature search using electronic databases such as PubMed, ProQuest, Science Direct, and Google Scholar. The literature review conducts on international journals published in the last five years, available in free full text and not the result of an examination. Results: Interventions for dealing with stunting at 1000 days of life can be in the form of interventions during the pre-conception period and pregnancy until the baby is two years old. Interventions related to improving nutritional status by providing maternal nutrition for 1000 days of life. Providing education to mothers can increase mothers' knowledge and care in preventing stunting. Conclusions: The intervention results showed that giving nutrition for 1000 Days of Life reduced stunting in rural areas. Providing education to mothers increases the knowledge of prospective mothers in preparing for healthy pregnancies and preventing stunting in children.